EFISIENSI OPERASIONAL DAN DINAMIKA MANAJEMEN ABK PADA KAPAL PURSE SEINE KM SINAR HARAPAN 88 DI PPN SIBOLGA - Sitompul, Nabila Khairiyah; Prayoga, Muhamad Yogi; Purba, Bima Theo Christian (Politeknik Kelautan dan Perikanan Karawang, BRSDM KP., 2025)
This study aims to analyze the operational efficiency and crew management dynamics on the purse seine vessel KM Sinar Harapan 88, based at the Nusantara Fisheries Port (PPN) in Sibolga. The main issue addressed is how onboard organizational structure and internal factors influence the effectiveness of the fishing process, particularly during the hauling stage, which consumes the most time. The research employed a participatory observation method over a 19-day active fishing voyage, combined with structured interviews involving 15 crew members and the captain. Quantitative data were analyzed using multiple linear regression to assess the influence of the number of active crew, setting duration, and weather conditions on hauling time. The results indicate that a well-structured workflow, clear task distribution, and efficient coordination significantly contribute to smooth vessel operations. The average duration of one fishing cycle (setting–hauling–handling) is approximately 2.5 hours, with hauling accounting for the largest portion of time (±43%). Regression analysis revealed that both the number of active crew members and setting duration had a statistically significant effect on hauling time (p < 0.05), whereas weather conditions did not show a statistically significant impact. These findings emphasize that operational efficiency on purse seine vessels is more strongly influenced by human.